La Guyane, un territoire Caraïbe en voie de sud-américanisation - Stéphane Granger (EchoGéo)
On the north coast of South America, French Guiana is appearing more as a caribbean territory because his history, his historical culture and his political and economical relations. But the high standard of living allowed by the french and european statute is transforming it as an outlet for ten of thousands of immigrants natives of the bordering Brazil and more and more Peru, inducing a sudden awareness of his situation of interface between the Caribbean world, South America and Europa. The recent admission of France as observer in the Organization of the Amazonian Cooperation Treaty owing to French Guiana is proving the new interest for this french country in America. But political statute, social and economical differences and mentalities are obstructing a greater integration in his geographical surroundings.